PENGGUNAAN MEDIA SOSIAL DAN INTENSITAS BELAJAR SISWA MA MUHAMMADIYAH PEKANBARU - Sumarni Sumarni; Elni Yakub; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : A phenomenon seen recently about the use of social media that affects the intensity of student learning Such as are playing mobile phone, accesing social media and updating the status or uploading the photos to the social media while the learning prosess is done and more often access social media than learning. This study aims to find out: 1) The types of social media they use, 2) The description of the intensity of accessing social media, 3) The purpose of the use of social media by students, 4) description of student learning intensity of social media users. This was a quantitative descriptive research design. The population of the research was all students whose using social media at MA Muhammadiyah Pekanbaru. Then, in determining the sample, the researcher used saturated sampling technique. The total number of the sample was 92 students. In collecting the data the researcher used questionnaires with likert scale. In analysing the data the researcher use percentage technique. Based on the research findings, the results showed: 1) The types of social media used by many students was whatsapp, 2) The intensity of accessing social media is the students often access social media because of their interest to obtain information and to found out friends, 3) The purpose of using social media in school was to communicate , 4) The intesity of students learning whose using social media is more than half the students are still motivated to learn and remain excited school.Key words : Learning Intensity, Social Media